Pengaruh Pembelajaran Kontekstual terhadap Motivasi Belajar pada Pembelajaran B. Indonesia Siswa Kelas II MI Salafiyah 1 Kauman - I’anatul Ashriyah; Ani Ani (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to examine the effect of contextual learning on students’ learning motivation in Indonesian language learning for second-grade students of Madrasah Ibtidaiyah (MI) Salafiyah 1 Kauman. Contextual learning is an instructional approach that connects learning materials with students’ real-life experiences, which is expected to increase their engagement and learning motivation. This study employed a quantitative approach with an experimental research design. The subjects of the study were second-grade MI students divided into an experimental class and a control class. Data were collected through learning motivation questionnaires and classroom observations during the learning process. The collected data were analyzed using statistical techniques to determine differences in learning motivation between the two groups. The results indicate that contextual learning has a positive and significant effect on students’ learning motivation in Indonesian language learning. Students who were taught using contextual learning showed higher learning motivation than those who were taught using conventional learning methods. Therefore, contextual learning can be considered an alternative instructional strategy to enhance students’ learning motivation at the elementary or Madrasah Ibtidaiyah level.